FOXRED1 silencing in mice: a possible animal model for leigh syndrome. - Mohamed, Salama; El-Desouky, Sara; Alsayed, Aziza; El-Hussiny, Mahmoud; Moustafa, Abdelrahman; Taalab, Yasmeen M.; Mohamed, Wael Mohamed Yousef (Springer New York LLC, 2019)
Leigh syndrome (LS) is one of the most puzzling mitochondrial disorders, which is also known as subacute necrotizing encephalopathy. It has an incidence of 1 in 77,000 live births worldwide with poor prognosis. Currently, there is a poor understanding of the underlying pathophysiological mechanisms of the disease without any available effective treatment. Hence, the inevitability for developing suitable animal and cellular models needed for the development of successful new therapeutic modalities. In this short report, we blocked FOXRED1 gene with small interfering RNA (siRNA) using C57bl/6 mice. Results showed neurobehavioral changes in the injected mice along with parallel degeneration in corpus striatum and sparing of the substantia nigra similar to what happen in Leigh syndrome cases. FOXRED1 blockage could serve as a new animal model for Leigh syndrome due to defective CI, which echoes damage to corpus striatum and affection of the central dopaminergic system in this disease. Further preclinical studies are required to validate this model.